2013
DOI: 10.1099/mic.0.063065-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of two Pseudomonas aeruginosa anthranilate synthases in tryptophan and quorum signal production

Abstract: Pseudomonas aeruginosa is a Gram-negative, opportunistic pathogen that causes infections in the lungs of individuals with the genetic disease cystic fibrosis. Density-dependent production of toxic factors regulated by the Pseudomonas quinolone signal (2-heptyl-3-hydroxy-4-quinolone; PQS) have been proposed to be involved in P. aeruginosa virulence. PQS biosynthesis requires conversion of the central metabolite chorismate to anthranilate by anthranilate synthase. This reaction is also the first step in tryptoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…These results suggest that the transcript between pqsD, pqsE, and phnA is likely expressed only under nutritionally stressed conditions and further explained our previous results which indicated that PhnA could restore PQS to a kynurenine pathway mutant only under nutrient-limiting conditions (24). These data also nicely corroborate those of Palmer et al (30), who showed that overexpression of phnAB complements tryptophan auxotrophy and PQS production in a trpE mutant. Considering all of this, we believe that we have identified a unique natural transcript that allows for differential expression of phnAB when grown under different conditions.…”
Section: Figsupporting
confidence: 81%
See 1 more Smart Citation
“…These results suggest that the transcript between pqsD, pqsE, and phnA is likely expressed only under nutritionally stressed conditions and further explained our previous results which indicated that PhnA could restore PQS to a kynurenine pathway mutant only under nutrient-limiting conditions (24). These data also nicely corroborate those of Palmer et al (30), who showed that overexpression of phnAB complements tryptophan auxotrophy and PQS production in a trpE mutant. Considering all of this, we believe that we have identified a unique natural transcript that allows for differential expression of phnAB when grown under different conditions.…”
Section: Figsupporting
confidence: 81%
“…Though this enzyme seemingly could provide anthranilate for the cellular pool, TrpEG does not naturally provide anthranilate for PQS production in a phnA mutant grown without tryptophan (24). However, overexpression of TrpEG causes PQS production in a phnAB mutant grown without tryptophan, thus indicating the importance of phnAB regulation for PQS production (30).…”
mentioning
confidence: 99%
“…The identification of this gene was part of a massive biochemical screen of various bacterial BKACE members and proved very valuable for the identification of these CoA-dependent cleavage enzyme substrates (Bastard et al, 2014). The glycine betaine-CoA derived from BKACE activity is then converted to glycine betaine and CoA by a CoA transferase, likely the DhcAB enzyme in Pseudomonas aeruginosa (Wargo & Hogan, 2009), which appears to function as a general amino acid CoA transferase (Palmer et al, 2013). After carnitine is metabolized to glycine betaine, it can function as an osmolyte (as described above) or be utilized as a sole carbon, nitrogen, and energy source if the organism encodes the necessary enzymes, as in the case for Pseudomonas aeruginosa (Wargo et al, 2008) (Hwang & Bang, 1997), Rhizobium sp.…”
Section: Carnitine As a Nutrientmentioning
confidence: 99%
“…Anthranilate synthase (AS) [EC 4.1.3.27] catalyzes the production of anthranilate from chorismate in the l -tryptophan biosynthesis branch. ASs have been characterized in bacteria (Bae et al, 1989; Ito et al, 1969; Palmer, G.C. et al, 2013), in plants (Morino et al, 2005; Saika et al, 2012; Tozawa et al, 2001) and in Saccharomyces cerevisiae (Braus, 1991; Graf et al, 1993).…”
Section: Introductionmentioning
confidence: 99%